The influence of task-value scaffolding in a predictive learning analytics dashboard on learners' statistics anxiety, motivation, and performance. (November 2021) - Valle, Natercia; Antonenko, Pavlo; Valle, Denis; Dawson, Kara; Huggins-Manley, Anne Corinne; Baiser, Benjamin
Abstract: There is an increasing trend of learning analytics dashboards (LADs) being used to provide feedback to learners. However, there is little empirical evidence about the influence of their design features on learners' cognitive and affective outcomes, especially in high-anxiety courses such as statistics. To address this gap, this study employed a two-group experimental design applied to an authentic setting to assess the influence of task-value scaffolding in a LAD on learners' anxiety, motivation, and learning performance in an online statistics course. This semester-long experiment was implemented in two instances of the course offering (Fall/2019 and Spring/2020) and involved a total of 146 students. The results showed that task-value scaffolding had a negative impact on learners' computation anxiety and attitudes towards statistics in comparison to the control group. On the other hand, the treatment had no significant influence on other aspects of statistics anxiety, motivation, and learning outcomes. Taken jointly, these results suggest that the use of task-value scaffolding embedded in LADs can have detrimental effects on learners. More experimental studies are necessary to understand the positive and negative effects of LADs with motivational scaffolding. Highlights: Task-value scaffolding intervention increased computation anxiety. Task-value scaffolding intervention increased worth anxiety. Task-value scaffolding intervention did not influence learners' motivation. Task-value scaffolding intervention did not influence learning performance.